Mitochondrial mitophagy in mesenteric artery remodeling in hyperhomocysteinemia2. Issue 4 (23rd April 2014) - Familtseva, Anastasia; Kalani, Anuradha; Chaturvedi, Pankaj; Tyagi, Neetu; Metreveli, Naira; Tyagi, Suresh C.
Abstract: Although high levels of homocysteine also termed as hyperhomocysteinemia (HHcy) has been associated with inflammatory bowel disease and mesenteric artery occlusion, the mitochondrial mechanisms behind endothelial dysfunction that lead to mesenteric artery remodeling are largely unknown. We hypothesize that in HHcy there is increased mitochondrial fission due to altered Mfn‐2/Drp‐1 ratio, which leads to endothelial dysfunction and collagen deposition in the mesenteric artery inducing vascular remodeling. To test this hypothesis, we used four groups of mice: (i) WT (C57BL/6J); (ii) mice with HHcy (CBS+/−); (iii) oxidative stress resistant mice (C3H) and (iv) mice with HHcy and oxidative stress resistance (CBS+/−/C3H). For mitochondrial dynamics, we studied the expression of Mfn‐2 which is a mitochondrial fusion protein and Drp‐1 which is a mitochondrial fission protein by western blots, real‐time PCR and immunohistochemistry. We also examined oxidative stress markers, endothelial cell, and gap junction proteins that play an important role in endothelial dysfunction. Our data showed increase in oxidative stress, mitochondrial fission (Drp‐1), and collagen deposition in CBS+/− compared to WT and C3H mice. We also observed significant down regulation of Mfn‐2 (mitochondrial fusion marker), CD31, eNOS and connexin 40 (gap junction protein) in CBS+/− mice as compared to WT and C3H mice. In conclusion, our data suggested that HHcy increased mitochondrial fission (i.e., decreased Mfn‐2/Drp‐1 ratio, causing mitophagy) that leads to endothelial cell damage and collagen deposition in the mesenteric artery. This is a novel report on the role of mitochondrial dynamics alteration defining mesenteric artery remodeling. Abstract : e00283 This article is a novel report on the role of mitochondrial dynamics in mesenteric artery remodeling during hyperhomocysteinemia. The study can contribute significantly toward understanding the mesenteric mitochondrial mechanisms underpinning inflammatory bowel disease – a major clinical concern.